KEDUDUKAN ISTRI YANG DINIKAHI SECARA SIRI MENURUT HUKUM PERDATA DAN HUKUM ISLAM DALAM MEMPEROLEH HAK WARIS - Izwany, Bonita; Syahputra, Muhammad Herry (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
The purpose of this research is to find out the rights and positions of married wives in series in obtaining inheritance, the rights of married wives in series according to the Civil Law and Islamic Law that apply mainly based on the perspective of Civil Law and Islamic Law, and the legal impact arising from siri marriage in obtaining inheritance. To obtain data in writing this thesis, literature research was conducted. The results of the study are known that the position of the married wife in series according to the provisions of Civil Law and Islamic Law in promo tinging the right of inheritance is weak. Both Civil Law and Islamic Law have similarities and differences between the two legal systems, especially regarding the rights of married wives in series. The negative impact of siri marriage is very influential for wife and son not to mention the impacts that will be inflicted in the long run. It is recommended to create a legal and administrative order, so that the couple who want to perform the marriage in accordance with the provisions of religion and the prevailing laws and regulations so that there are no problems that will arise in the future. to the government to vigorously socialize the benefits of marriage recording and the impact of siri marriage especially on wives and children.